Elastic-plastic fracture mechanics study on interreacting cracks in engineering materials - Zhang, Dong (Nanyang Technological University, 2021)
Material failure is the consequence of improper usage or over-utilizing of the material. Unexpected material failures may result in serious consequences. Crack propagation is one of the biggest obstacles in causing unexpected material failures. However, cracks are ineliminable and it is formed either due to current manufacturing limitation or the concentrated force deformation at its working condition. Therefore, this work studies the growth and propagation mechanism for a crack from a notch and establishes the correlation of the crack to its geometry, external load, and material property. Moreover, this study has been extended to the effect of the crack from different types of notch under cyclic loading. With the help of the ANSYS 2020R2, the simulation is constructed to reveal the difference in the failure mechanism from 3 different scenarios in both 2D and 3D. In addition, the differences would be observed between different notched geometry and the number of loading cycles to reach its fatigue limit.